І-й відкритий з’їзд фітобіологів Херсонщини (Херсон, 6 квітня 2006 р.) - Бойко, М.Ф.; Ходосовцев, О.Є. (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
І-й відкритий з’їзд фітобіологів Херсонщини (Херсон, 6 квітня 2006 р.)